2010
DOI: 10.1186/1471-2156-11-56
|View full text |Cite
|
Sign up to set email alerts
|

Detection of quantitative trait loci affecting haematological traits in swine via genome scanning

Abstract: BackgroundHaematological traits, which consist of mainly three components: leukocyte traits, erythrocyte traits and platelet traits, play extremely important role in animal immune function and disease resistance. But knowledge of the genetic background controlling variability of these traits is very limited, especially in swine.ResultsIn the present study, 18 haematological traits (7 leukocyte traits, 7 erythrocyte traits and 4 platelet traits) were measured in a pig resource population consisting of 368 pureb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…A significant QTL for HGB was also mapped to the same region, suggesting a common genetic regulation of the four traits. The QTL affecting HGB overlaps with the region reported by Zou et al (2008), whereas the three QTL for MCV, MCH and MCHC overlap with the region reported by Gong et al (2010). This study revealed a highly significant QTL affecting MCV on SSC13, which accounted for 3.3% of the phenotypic variance and overlaps with the QTL for MCV identified by Gong et al (2010).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…A significant QTL for HGB was also mapped to the same region, suggesting a common genetic regulation of the four traits. The QTL affecting HGB overlaps with the region reported by Zou et al (2008), whereas the three QTL for MCV, MCH and MCHC overlap with the region reported by Gong et al (2010). This study revealed a highly significant QTL affecting MCV on SSC13, which accounted for 3.3% of the phenotypic variance and overlaps with the QTL for MCV identified by Gong et al (2010).…”
Section: Resultssupporting
confidence: 59%
“…In contrast, only a limited number of QTL analyses of haematological traits (i.e. leucocyte, platelet and erythroid traits) have been performed in pigs (Wattrang et al 2005;Reiner et al 2007Reiner et al , 2008Zou et al 2008;Yang et al 2009;Gong et al 2010). Leucocyte count is a potent indicator of defence-related disorders, such as infectious diseases, because leucocytes are a component of the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…; Gong et al . ), suggesting that alleles of QTL for WBC may vary among breeds or populations. However, the QTL for WBC on SSC2, detected in our study, is located in a similar position to a QTL for WBC identified previously in a White Duroc × Erhualian F2 resource population (Yang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Only one study, Gong et al . (), has detected QTL affecting immune response in a purebred population, and this study examined haematological traits.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the LR test statistic is defined as LR  =  L ( QTL )/ L ( polygenic ) where L(QTL) is the likelihood of the full model that includes the polygenic and QTL effects. The nominal P -value was estimated assuming the LR test statistic follows a chi-square distribution with two degrees of freedom [43]. The genome-wide significance level of detected QTL was also estimated as P GenomeWide  = 1 − (1 −  P ) g [37] where P is the nominal P -value, and g = 365 STR loci used with LDLA analysis.…”
Section: Methodsmentioning
confidence: 99%